¿Posee la ética un fundamento objetivo? Reflexiones desde Wittgenstein sobre el problema de explicar los juicios de valor (2015)
In this article we use different contributions of Ludwig Wittgenstein (primary and secondary sources) in order to critically analyze common ideas about the origins and foundations of our ethical judgments. For this, we argue that the distinction made by the philosopher between reasons and causes is relevant to show that ethical values have no natural or objective foundation. Valuations, however, rely on reasons arising from a sociocultural system and are constituted through language. Thus, we propose that the concept of “language games” proposed by Wittgenstein, can better allow an understandimg of how individuals internalize rules and criteria from which ethical judgments are made and moral principles are established.